Cyclophosphamide-Free Adjuvant Chemotherapy for Ovarian Protection in Young Women With Breast Cancer: A Randomized Phase 3 Trial. (2nd April 2021) - Yu, Ke-Da; Ge, Jing-Yu; Liu, Xi-Yu; Mo, Miao; He, Min; Shao, Zhi-Ming; ,
Abstract: Background: Chemotherapy-induced premature menopause leads to some consequences, including infertility. We initiated this randomized phase III trial to determine whether a cyclophosphamide-free adjuvant chemotherapy regimen would increase the likelihood of menses resumption and improve survival outcomes. Methods: Young women with operable estrogen receptor-positive HER2-negative breast cancer after definitive surgery were randomly assigned to receive adjuvant epirubicin and cyclophosphamidefollowed by weekly paclitaxel (EC-wP) or epirubicin and paclitaxel followed by weekly paclitaxel (EP-wP). All patients received at least 5-year adjuvant endocrine therapy after chemotherapy. Two coprimary endpoints were the rate of menstrual resumption at 12 months after chemotherapy and 5-year disease-free survival in the intention-to-treat population. This study is registered at ClinicalTrials.gov (NCT01026116). All statistical tests were 2-sided. Results: Between January 2011 and December 2016, 521 patients (median age = 34 years; interquartile range = 31-38 years) were enrolled, with 261 in the EC-wP group and 260 in the EP-wP group. The rate of menstrual resumption at 12 months after chemotherapy was 48.3% in EC-wP (95% confidence interval [CI] = 42.2% to 54.3%) and 63.1% in EP-wP (95% CI = 57.2% to 68.9%), with an absolute difference of 14.8% (95% CI = 6.37% to 23.2%, P  < .001). The posthoc exploratory analysis by patient-reported outcome questionnaires indicated that pregnancy might occur in fewer women in the EC-wP group than in the EP-wP group. At a median follow-up of 62 months, the 5-year disease-free survival was 78.3% (95% CI = 72.2% to 83.3%) in EC-wP and 84.7% (95% CI = 79.3% to 88.8%) in EP-wP (stratified log-rank P  = .07). The safety data were consistent with the known safety profiles of relevant drugs. Conclusions: The cyclophosphamide-free chemotherapy regimen might be associated with a higher probability of menses resumption.